KEPASTIAN HUKUM DALAM PEMBUKTIAN PERKARA PEMBATALAN PENETAPAN PERKAWINAN PADA PUTUSAN PENGADILAN TINGGI DKI JAKARTA NOMOR 139/PDT/2020/PT. DKI - Hana Nabilah Putri; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2021)
The risk of burden can encourage the parties to compete in proving who is the most correct so they are willing to do various ways such as submitting evidence that has been falsified in order to fulfill their desire to be able to win cases in court Problems regarding this can be found to date, one of which is in the case of the start of the determination which is still in the High Court Decision Number 139/PDT/2020/PT.DKI. The decision made by the judge was the stipulation of marriage between Mutiawa Lurin and Lukman Tjoe because Nina's side could prove that Mutiawa Lurin was not the only wife of Lukman Tjoe based on evidence that did not match reality. The problem in writing this number is how legal certainty is in proving the case for the determination of marriage in the decision of the DKI Jakarta High Court 139/PDT/2020/PT.DKI. The research method used by the author is a normative research type which has a descriptive analytical research character with a normative juridical approach, based on primary legal sources, secondary legal sources obtained from library techniques and also supported by interviews. Basically marriage for parties who adhere to Christianity cannot be considered as monogamous, if a husband commits an act of polygamy then the marriage can be said to be valid by referring to the legal requirements of marriage contained in Article 2 paragraph (1) of Law Number 1 of 1974 And, in creating a decision that can realize legal certainty and justice, the judge is obliged to always be thorough and careful in examining the cases submitted to him.